Penerapan Teknik Relaksasi Benson Pada Pasien Dengan Nyeri Akut Akibat Post Operasi Transurethral Resection Of The Prostate Atas Indikasi Benigna Prostat Hyperplasia - Oom Komariyah; Dwiyanti Purbasari; Diana Sari; Risma Fitriyani; Khaerunnisa Dwi Hikmatun (MEJORA Medical Journal Awatara, 2024)
One of the surgical procedures for patients with Benign Prostatic Hyperplasia (BPH) is Transurethral Resection of the Prostate (TURP). This procedure often causes postoperative pain in the lower abdominal area or around the pubic symphysis. Benson relaxation technique is a non-pharmacological pain management approach that helps alleviate mental and physical tension as well as stress, thereby increasing pain tolerance. This study aims to determine the effect of the Benson relaxation technique in reducing acute pain in postoperative patients with Benign Prostatic Hyperplasia (BPH) at Waled Regional General Hospital, Cirebon Regency. The study employed a case study design with a nursing process approach on one respondent who underwent TURP surgery one day earlier due to BPH. Benson relaxation therapy was administered on the second to fourth postoperative days. Pain was assessed using the Numeric Rating Scale (NRS) and qualitative pain evaluation. The study was conducted in December 2023. By the fourth postoperative day, the patient reported mild pain characterized by a stabbing sensation around the surgical wound in the abdomen. The pain was intermittent, particularly when getting out of bed, moving, or engaging in physical activity. The pain scale was 3, and the patient appeared calm and relaxed, with a pulse rate of 84 beats per minute and a respiratory rate of 18 breaths per minute during activities without supplemental oxygen. Continuous application of the Benson relaxation technique can serve as a complementary intervention to reduce acute pain in postoperative TURP patients due to BPH.